RETRACTED: Lyceum coworking as a motivator for students to work together - Belousov Oleg; Shefer Olga; Kraineva Svetlana; Lebedeva Tatyana (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001